RELATIONSHIP OF EXPRESSION LEVEL OF TWO YIELD RELATED GENES WITH MORPHO-AGRONOMIC VARIABILITY IN COMPOSITE CORN LINES UNDER DRY CLIMATE - F. Abna; F. A. Avin; F. Baysal-Gurel; N. W. Haron (Journal of Animal and Plant Sciences, 2022)
The grain harvest in corn is measurable and controlled polygenically. Therefore, effective yield enhancement and concurrent modification of yield-related genes are imperative. Six newly composite corn lines were characterized and their morpho-agronomic variability was evaluated. The expression level of two yield-related genes (Sh2 and Bt2b) and their relationship with morpho-agronomic characters were considered using quantitative real-time PCR (qRTPCR). The outcomes of the principal component analysis showed that 2 components with Eigen values larger than one explained 86.62 percent of the total variability. The highest phenotypic and genotypic coefficients of variance (PCV and GCV, respectively) were recorded for grain yield per plant. The greatest phenotypic and genotypic correlation of grain yield per plant was noted with 1000- kernel weight (0.84 and 0.98, respectively). Kernel number showed the highest genetic advance (1990.12%) and heritability (75.27%). Kernel number and its 1000 weights were positively correlated with grain yield per plant. The Sh2 and Bt2b genes presented upregulated expressions in leaf and endosperm tissues which was significantly and positively related to the grain yield and its primary components. It was observed that by altering the expression level of Sh2 and Bt2b genes via hybridization in the composite corn lines, yield enhancement and improvement in genetic parameters of yield components occurred.
Keywords: cross transformation; morpho-agronomic variability; yield-related genes